Avicenna's Canon of Medicine: a review of analgesics and anti-inflammatory substances - Mahdizadeh, Shahla (Avicenna J Phytomed, 2015)
Naturally occurring substances mentioned in medieval medical literatures currently have, and will continue to have, a crucial place in drug discovery. Avicenna was a Persian physician who is known as the most influential medical writers in the Middle ages. Avicenna`s Canon of Medicine, the most famous books in the history of medicine, presents a clear and organized summary of all the medical knowledge of the time, including a long list of drugs. Several hundred substances and receipts from different sources are mentioned for treatment of different illnesses in this book. The aim of the present study was to provide a descriptive review of all anti-inflammatory and analgesic drugs presented in this comprehensive encyclopedia of medicine. Data for this review were provided by searches of different sections of this book. Long lists of anti-inflammatory and analgesic substances used in the treatment of various diseases are provided. The efficacy of some of these drugs, such as opium, willow oil, curcuma, and garlic, was investigated by modern medicine; pointed to their potent anti-inflammatory and analgesic properties. This review will help further research into the clinical benefits of new drugs for treatment of inflammatory diseases and pain.